Gray's anatomy for students - Drake, Richard L., Ph.D.; Vogl, Wayne; Mitchell, Adam W. M.; Gray, Henry, 1825-1861.; Gray, Henry, 1825-1861. (Philadelphia, PA : Churchill Livingstone/Elsevier, 2010)
"Only in its second edition, this highly popular, clinically focused textbook has made a huge impact with students worldwide. A team of authors with a wealth of diverse teaching and clinical experience has updated and revised this new edition to efficiently cover what you're learning in contemporary anatomy classes. Unique coverage of surface anatomy, correlative diagnostic images, and clinical case studies demonstrate practical applications of anatomical concepts. And an international advisory board, comprised of more than 100 instructors, ensures that the material is accurate, up to date, and easy to use."--BOOK JACKET.
The body -- Back -- Thorax -- Abdomen -- Pelvis and perineum -- Lower limb -- Upper limb -- Head and neck.
Includes index.
Keywords: Human anatomy; Anatomy